T-BET drives the conversion of human type 3 innate lymphoid cells into functional NK cells - Kiekens, Laura; Wahlen, Sigrid; Persyn, Eva; De Vos, Zenzi; Taghon, Tom; Vandekerckhove, Bart; Leclercq, Georges (Frontiers in Immunology, 2022)
Type 3 innate lymphoid cells (ILC3s) are characterized by RORγt expression and they produce IL-22 upon activation. ILC3s play a role in maintenance of barrier integrity in the intestine. Under inflammatory conditions, the ILC composition of the mucosal tissues is altered due to a high degree of plasticity. It has been extensively demonstrated that both murine and human ILC3s convert into ILC1s to mediate appropriate immune responses. However, plasticity between human ILC3s and NK cells is less well documented. As T-BET and EOMES are key transcription factors in NK cell differentiation, we investigated whether ectopic T-BET or EOMES expression converts human ILC3s into NK cells. ILC3s with ectopic T-BET and EOMES expression downregulate RORγt expression, while T-BET-overexpressing ILC3s additionally upregulate EOMES expression. High ectopic T-BET expression in ILC3s results in transdifferentiation towards CD94+ NK cells, whereas ectopic EOMES overexpression results in dedifferentiation of ILC3s into CD94-CD117-/low cells, but is ineffective in NK cell generation. Dedifferentiating ILC3s from both T-BET and EOMES overexpression cultures readily upregulate NK cell receptors,perforin and granzyme B,. Finally, IL-22 secretion is completely blocked in transdifferentiating ILC3s with both T-BET and EOMES ectopic expression, whereas only T-BET overexpression increases IFN-γ secretion and cytotoxicity. Altogether, these findings demonstrate that human ILC3s can convert into functional NK cells, wherein T-BET, and not EOMES, is the main driver.